Sampling mobility index: Case study in Assis - Brazil - Frei, Fernando (Elsevier B.V., 2006)
The objective of this work is to present an index which may synthesize a set of indicators of mobility for medium size cities urban centers. Three great areas were selected to compose the mobility index: pedestrians, motor vehicles and cycling. The Sampling Mobility Index is given by the sum of the punctuation the indicators selected and can to result in 700 points, the best result to mobility, and 0 points, the worse to mobility. The result obtained is given by the Sampling Mobility Index equal to 390. This result indicates a critical situation in Assis, as far as mobility is concerned. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: mobility; index; indicators; urban centers